The interdependent relationship between sectoral productivity and disaggregated energy consumption in Malaysia: Markov Switching approach - Rahman, M.S.; Shahari, Farihana; Rahman, Mahfuzur; Md Noman, Abu Hanifa (Elsevier B.V., 2017)
This study examines the interdependent relationship between sectoral productivity and disaggregated energy consumption in Malaysia by employing the Markov Switching technique. Several outcomes were reached. Firstly, the regime movement of GDP during regime-2 is influenced by disaggregated energy consumption. Secondly, the regime-1 and regime-2 of industrial and manufacturing productivity are responded by the respective regimes of disaggregated energy consumption. Finally, the regimes of carbon emission depend on both of manufacturing and industrial productivity. This study recommends to consume the energy at an efficient level and green technology in order to minimise energy consumptions and environment pollution.